(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
Highlighting women’s socioeconomic empowerment through microfinance is the aim of this research paper. The design of the study is descriptive. Although society does a lot of developmental activities and programs, microfinance programs are particularly effective in rural areas, focusing on disadvantaged women and the underprivileged population. Microfinance is a potent and successful tool for empowering women. By increasing their income through small initiatives, women who were able to access microfinance services have been able to empower themselves both economically and socially and generate prospects for self-employment. The impact of microfinance services on the empowerment of Nepali women residing in the Baijanath Rural Municipality Banke was investigated in this thesis. The economic standing, decision-making ability, knowledge, and self-worth of women, as well as community activities and self-help group programs, are all significantly impacted by microfinance. Decision-making in the family, social and political involvement, how society views them, social awareness, health and sanitation awareness, and improved livelihood were all factors in social empowerment. The ladies of Baijanath Rural Municipality completed a standardized questionnaire that provided the primary data for this study. In addition to being described by tables and figures, data are examined using percentage analysis. Using a straightforward random sample technique, descriptive research design has been utilized to gather respondents’ thoughts and learn about their behavior. This study examines how women’s decision-making abilities and social participation increase following their participation in MFPs. All variables have a beneficial impact, according to the results. Of women, 58.18 percent own their own land, 53.64 percent work in retail, and 45.45 percent make up to Rs 10,000 a month. Similarly, 48.64 percent of women own a television, and 23.64 percent have access to the internet. With a 62.73 percent success rate, MFP training has a very beneficial effect. After joining MFP, 49.10 percent of women report much better family relationships. 53.64 percent of women make decisions about their children’s education, and 74.45 percent make decisions about their medical care. According to the study’s findings, microfinance institutions benefit women by enhancing their social well-being, access to and control over their resources, investment and consumption, self-confidence, and capacity for making decisions both within and outside of the family.